Regional Convergence in the European Union: What are the Factors of Growth? - Jan Pintera (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Despite years of deepening economic integration among the states and regions of the European Union, empirical research remains inconclusive about speed of convergence across regions, if not its existence. This paper provides a new look on convergence in the EU while focusing on development at regional level after the Great Recession. It uses the log t convergence test by Phillips and Sul (2007) to analyze the convergence in level of income among the European regions. Rather than supporting the convergence hypothesis, we identify five convergence clubs in which the regions converge in income growth rates. Investigating further the geographical distribution of the convergence clubs, we confirm high inequality within the member states and find large continuous area of high convergence clubs in the urbanized part of Western Europe. Furthermore, we investigated the determinants of convergence club membership using Logistic Regression. We found a low impact of any of the estimated variables on membership in the highest club but confirmed positive association of membership in the higher clubs with research and patent activities.
Keywords: C23; C40; R11; 330; Club Convergence; European Regions; log t test; Logistic regression